2020
DOI: 10.1111/and.13556
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma vitamin B 6 levels in men with asthenozoospermia and men with normal sperm motility, a measurement using liquid chromatography with tandem mass spectrometry

Abstract: There is growing evidence that vitamin B6 has a valuable contribution in maintaining normal sperm parameters; however, this contribution has not yet well‐identified. Here, we aimed to measure the level of seminal plasma vitamin B6 in men with asthenozoospermia compared to men with normal sperm motility. Ninety‐seven human males with asthenozoospermia and eighty‐eight human males with normal sperm motility (control) were recruited in this study. Collected semen samples were assessed for sperm motility, sperm co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Folic acid is also reported to significantly increase sperm density in patients with oligospermia or asthenospermia [33]. On the contrary, so far, no statistical correlations have been found between the amount of seminal plasma vitamin B6 and the seminal parameters [34]. Moreover, vitamin D is also directly implicated in ameliorating the semen quality and sperm motility, male reproductive potential, and testosterone levels [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid is also reported to significantly increase sperm density in patients with oligospermia or asthenospermia [33]. On the contrary, so far, no statistical correlations have been found between the amount of seminal plasma vitamin B6 and the seminal parameters [34]. Moreover, vitamin D is also directly implicated in ameliorating the semen quality and sperm motility, male reproductive potential, and testosterone levels [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Probably, this is due to the ability of vitamin D to promote the synthesis of ATP through the cAMP/PKA pathway [36]. However, to date, the role of vitamin D and other vitamins in male fertility still remains debated [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that sperm cells are transcriptional and translational inert cell, we suggest that differential metabolites enriched in the first pathway may reflect sperm cells binding to proteins from extracellular vesicles ( EV ) ( Morgan et al, 2021 ). Vitamin B6 plays an important role in maintaining normal sperm parameters ( Banihani and Aljabali, 2020 ). In human studies, men with asthenozoospermia have lower seminal plasma vitamin B6 level compared with men having normal sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…A newly published study on rat varicocele model concluded that vitamin B complex, including pyridoxine, administered at 6 mg kg −1 , is efficient to enhance the parameters of sperm, particularly count and motility [ 27 ]. Recently, in the previous work, we have shown that men with only asthenozoospermia had lower seminal pyridoxine concentration compared to those with normal motility of sperm [ 23 ]. These findings, albeit partially, are in line with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in 2017, it was concluded that in vitro research studies as well as clinical trials that reveal the influence of pyridoxine on human semen quality are highly required [ 15 ]. Accordingly, in the first set of this demanded research context, as a long-term goal to explore basically and clinically the impact of pyridoxine on semen quality, we have shown that men with asthenozoospermia had lower SPP level compared to those with normal motility of sperm [ 23 ]. Further, in this work, as an added important contribution, we asked whether seminal plasma pyridoxine (SPP) level is different in males with oligozoospermia compared to normozoospemic males, also, using the analytically sensitive ultra-high-performance liquid-chromatography tandem-mass spectrometry (ultra-LC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%